PH-sensitive inulin-based nanomicelles for intestinal site-specific and controlled release of celecoxib. (1st February 2018) - Mandracchia, Delia; Trapani, Adriana; Perteghella, Sara; Sorrenti, Milena; Catenacci, Laura; Torre, Maria Luisa; Trapani, Giuseppe; Tripodo, Giuseppe
Highlights: INVITESA micelles as pH-sensitive systems for oral delivery of hydrophobic drugs. The drug loading stabilizes the micelles against acidic hydrolysis. Despite a 1% release at pH 1.2 the whole drug was released in 10 h at pH 6.8. Transport studies on Caco-2 cells monolayers demonstrated Pgp involvement. Abstract: Aiming at a site-specific drug release in the lower intestinal tract, this paper deals with the synthesis and physicochemical/biological characterization of pH-sensitive nanomicelles from an inulin (INU) amphiphilic derivative. To allow an intestinal site specific release of the payload, INU-Vitamin E (INVITE) bioconjugates were functionalized with succinic anhydride to provide the system with pH-sensitive groups preventing a premature release of the payload into the stomach. The obtained INVITESA micelles resulted nanosized, with a low critical aggregation concentration and the release studies showed a marked pH-dependent release. The drug loading stabilized the micelles against the acidic hydrolysis. From transport studies on Caco-2 cells, resulted that INVITESA nanomicelles cross the cellular monolayer but are actively re-transported in the secretory (basolateral-apical) direction when loaded in apical side. It suggests that the entrapped drug could not be absorbed before the release from the micelles, enabling so a local release of the active.